The Role of Self-Efficacy in Mediating Workload, Career Development, Leadership, and Employee Productivity in Coffee Shops - Anisa Anisa; Suhardi Suhardi; Mat Amin (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
The rapid growth of the coffee shop industry in Indonesia has intensified competition in the food and beverage sector, making employee productivity essential for maintaining service quality and operational effectiveness. In dynamic service environments, employees are often required to handle demanding workloads, multitasking responsibilities, and continuous customer interactions, highlighting the importance of psychological factors in influencing performance. This study examines the effects of workload, career development, and leadership on employee productivity, with self-efficacy serving as a mediating variable among coffee shop employees in Pangkalpinang, Indonesia.A quantitative approach with a cross-sectional design was employed. Data were collected from 150 employees through purposive sampling, with respondents having at least six months of work experience. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software.The results show that workload has a positive and significant effect on self-efficacy, while self-efficacy significantly improves employee productivity. Self-efficacy also mediates the relationship between workload and productivity. Conversely, career development and leadership do not significantly influence either self-efficacy or productivity. These findings suggest that employees’ confidence in their abilities and psychological readiness play a more substantial role in enhancing productivity than traditional organizational mechanisms within informal service industries. The study contributes to the literature by extending social cognitive theory to the coffee shop context and emphasizing the role of self-efficacy as a key psychological mechanism linking workload and productivity. Practically, managers should strengthen employees’ psychological capabilities through coaching, peer support, workload balancing, and confidence-building initiatives.